The design of a numerically controlled drilling system using fluidic elements 1966/7 - Powell, E. A.; Boshier, G. C. (College of Aeronautics, 1967)
This report outlines the aims of the project and procedures used to bring it to a successful conclusion. It also summarises the results of an investigation into the parameters which govern the specification of a numerically controlled point to point drilling machine.